Projeto regulatório para a criação de uma política de consensualidade no município de Belém: edição de instrumento normativo como meio de implantação de uma política pública de desjudicialização - FREITAS, Bruno Cezar Nazaré de (Universidade Federal do Pará, 2023)
The present study aims to develop a Regulatory Project to create a consensuality policy in the Municipality of Belém. Public entities are some of the main litigants in Brazilian Justice. Improving conflict resolution mechanisms in which such entities are involved, therefore, represents an activity of utmost importance for the realization of rights, especially in a State like Brazil that has a series of obligations granted to the Public Power. Therefore, the publication of a normative instrument is essential to initiate a safe and efficient policy of dejudicialization in this city. In order for this objective to be achieved, extensive bibliographic and documentary research was carried out with the analysis of the main legal concepts linked to the topic and the numerous normative acts of the Union, States and capitals. The objective is to find out which entities have bodies for consensual dispute resolution, which legislative instrument is used to create such a structure, which bodies comprise it, what are the criteria for selecting cases and whether there is any difference in the procedures in relation to the nature of the case. right involved. The research concluded that the Union, most States and most Municipalities have bodies designed to resolve their conflicts administratively, as well as that they created their structures through complementary or ordinary laws in the structure of the Prosecutor's Office itself. It also allowed the identification of several case selection criteria, among them, the trinomial represented by the probability of success, advantage and technical, legal and operational feasibility of the agreement as appropriate requirements for identifying the hypotheses of possible agreements. The research was carried out using the hypothetical-deductive and action-research-technical methods, as it started from an existing problem, the selection of hypotheses, existing practices and the researcher's own professional experience to develop a regulatory model for this city. . The proposed regulation consists of a Bill that establishes a policy of consensuality in this city, a Project to modify the Decree that authorizes an agreement on court orders, a proposal for a Resolution from the Superior Council to regulate extrajudicial conflict resolution procedures and a Service Order to carry out pilot agreements on three topics selected from the process stock.